Dataset to: Deforestation for agriculture leads to soil warming and enhanced litter decomposition in subarctic soils ... - Peplau, Tino; Poeplau, Christopher; Gregorich, Edward; Schroeder, Julia (Zenodo, 2022)
Deforestation for agriculture leads to soil warming and enhanced litter decomposition in subarctic soils T. Peplau, C. Poeplau, E. Gregorich, J. Schroeder This repository contains a dataset of soil temperature, soil parameters, farm management and additional site informations. Soil_temperature_data_Yukon.zip: Temperature data from different farms across the Yukon. Each .xlsx file contains data from one temperature logger that logged soil temperature every 2 hours. The individual sheets are named in the following scheme: Farm_landuse_depth.xlsx Farm contains two letters corresponding to the identifier in the soil data set landuse contains either F ("Forest"), CM ("Cropland / Market Garden") or G ("Grassland") Depth is either 10 cm or 50 cm teabags.csv contains raw data about the initial weight of the teabags buried, their location and their weight after two years in the soil tea_decomposition contains the mean decomposition (n=3) of the tabags from each plot and corresponding temperature statistics, based on ...